Analisis Pengaruh Penduduk dan Pertumbuhan Ekonomi Terhadap Pengangguran di Provinsi Papua - Muhammad Misbath Falah; Mesak Iek (Universitas Cenderawasih, 2023)
This study investigates the relationship between population growth, economic growth, and unemployment in Papua Province, Indonesia, over the period 2010–2020. Contrary to the predictions of Okun’s Law, economic growth in resource-rich and structurally constrained regions may not necessarily translate into employment generation. Using secondary time-series data from the Central Bureau of Statistics and applying a multiple linear regression model, the results reveal that population growth has a positive and statistically significant effect on unemployment. In contrast, economic growth exhibits a negative but statistically insignificant effect on unemployment . These findings indicate weak employment elasticity of growth and suggest the presence of Jobless Growth. The study highlights structural limitations in Papua’s economy, where growth is dominated by capital-intensive sectors with low labor absorption. Policy implications emphasize the need to promote labor-intensive industries and enhance human capital to achieve inclusive and employment-generating growth. Keywords: economic growth, unemployment, population, jobless growth, Papua